AAV process intensification by perfusion bioreaction and integrated clarification - Mendes, João P.; Fernandes, Bárbara; Pineda, Earl; Kudugunti, Shashi; Bransby, Mike; Gantier, René; Peixoto, Cristina; Alves, Paula M.; Roldão, António; Silva, Ricardo J. S. (Frontiers in Bioengineering and Biotechnology, 2022)
Adeno-associated viruses (AAVs) demand for clinical trials and approved therapeutic applications is increasing due to this vector's overall success and potential. The high doses associated with administration strategies challenges bioprocess engineers to develop more efficient technologies and innovative strategies capable of increasing volumetric productivity. In this study, alternating tangential flow (ATF) and Tangential Flow Depth filtration (TFDF) techniques were compared as to their potential for (i) implementing a high-cell-density perfusion process to produce AAV8 using mammalian HEK293 cells and transient transfection, and (ii) integrating AAV harvest and clarification units into a single step. On the first topic, the results obtained demonstrate that AAV expression improves with a medium exchange strategy. This was evidenced firstly in the small-scale perfusion-mocking study and later verified in the 2 L bioreactor operated in perfusion mode. Fine-tuning the shear rate in ATF and TFDF proved instrumental in maintaining high cell viabilities and, most importantly, enhancing AAV-specific titers (7.6x104 VG/cell), i.e., up to 4-fold compared to non-optimized perfusion cultures and 2-fold compared with batch operation mode. Regarding the second objective, TFDF enabled the highest recovery yields during perfusion-based continuous harvest of extracellular virus and lysate clarification. This study demonstrates that ATF and TFDF techniques have the potential to support the production and continuous harvest of AAV, and enable an integrated clarification procedure, contributing to the simplification of operations and improving manufacturing efficiency.